Simple, Single-Shot Phosphoproteomic Analysis of Heat-Stable Tau Identifies Age-Related Changes in pS235- and pS396-Tau Levels in Non-human Primates - Leslie, Shannon N.; Kanyo, Jean; Datta, Dibyadeep; Wilson, Rashaun S.; Zeiss, Caroline; Duque, Alvaro; Lam, TuKiet T.; Arnsten, Amy F. T.; Nairn, Angus C. (Frontiers in Aging Neuroscience, 2021)
Age is the most significant risk factor for Alzheimer’s Disease (AD). Better understanding the role that aging plays in AD pathology is critical for therapeutic development. Neurofibrillary tangles (NFTs) composed of hyperphosphorylated tau are a quintessential hallmark of AD. We developed a simple, antibody-free approach for single shot analysis of tau phosphorylation across the entire protein by liquid-chromatography tandem mass spectrometry (LC-MS/MS) to study age-related changes in tau phosphorylation. This methodology is species independent; thus, while initially developed in a rodent model, we utilized this technique to analyze 36 phosphorylation sites on rhesus monkey tau from the prefrontal cortex (PFC), a region vulnerable to AD-linked degeneration. Data are available via ProteomeXchange with identifier PXD027971. We identified novel, age-related changes in tau phosphorylation in the rhesus monkey PFC and analyzed patterns of phosphorylation change across domains of the protein. We confirmed a significant increase and positive correlation with age of phosphorylated serine 235 tau and phosphorylated serine 396 tau levels in an expanded cohort of 14 monkeys. Histology showed robust labelling for tau phosphorylated at these sites in vulnerable layer III pyramidal cells in the PFC. The results presented in this study suggest an important role of the natural aging process in tau phosphorylation.